Effect of Cow Rumen Substrate Addition on Anaerobic Digestion Efficiency Under Acidic Conditions - Vikhory Bagus Wahyu Nugroho; Aussie Amalia; Rizka Novembrianto (JOBC, 2025)
Organic waste management has become a significant issue, particularly with the increasing amount of waste generated from agricultural, livestock, and household activities. One of the most widely applied technologies is the biodigester, which utilizes anaerobic digestion to decompose organic matter into compost and biogas. However, conventional biodigesters often face limitations in methane production efficiency, which is strongly influenced by substrate quality and microbial diversity. Rumen substrate from cows contains cellulolytic and methanogenic microbial communities that play a key role in accelerating the degradation of complex organic matter and enhancing methane production. This study aimed to investigate the impact of varying rumen substrate amounts on the performance of biodigesters. Three treatments were applied: no rumen addition, addition of 1 Kg, and addition of 2 Kg. Parameters observed included C/N ratio, pH stability, and methane gas percentage during a 35-day anaerobic fermentation period. The results showed that the biodigester with 1 Kg of rumen achieved a C/N ratio of 21.23, which falls within the optimal range of 20–30. Meanwhile, the biodigester with 2 Kg of rumen produced the highest methane percentage, reaching 0.0185% v/v on day 14, although production gradually declined thereafter. Overall, the addition of rumen was proven to improve the C/N ratio, stabilize pH, and enrich microbial communities, thereby enhancing methane production efficiency. These findings suggest that rumen substrate can be considered a potential co-substrate to enhance biodigester performance and facilitate sustainable organic waste management.